Tawakal and Academic Stress in Assignment Completion of University Students - Latif Nur Amalia; Ahmad Saifuddin (Faculty of Psychology, Universitas Gadjah Mada, 2022)
Academic stress is a condition experienced by any university student. However, academic stress can be a significant problem if it disrupts daily activities and incites maladaptive responses. This paper aimed to understand the correlation between tawakal and academic stress in assignment completion among students of UIN Raden Mas Said Surakarta. The study used a quantitative approach with a correlational method. The sampling method in this study was cluster random sampling involving 320 students of UIN Raden Mas Said Surakarta, aged 18 to 22 years old, from both genders. It utilized two measuring instruments namely: a) stress academic scale based on Sarafino and Smith’s theory with a reliability coefficient of 0.926, and b) tawakal scale based on Ibnu Qayyim’s theory with a reliability coefficient of 0.946. The data analysis technique implemented in the present study was Spearman’s correlation technique resulting in r=-0.103 and p=0.033 (p<0.05). Based on regression analysis between every aspect of tawakal with academic stress, there are three aspects of tawakal that contribute significantly to reducing academic stress, namely understanding the law of cause and effect (p=0,006), strengthening qalbu and tauhid (p=0,032), and leaving everything to Allah (p=0.000) Based on the analysis, there is a negative correlation between tawakal and academic stress in assignment completion among students of UIN Raden Mas Said Surakarta. Thus, tawakal can become a solution to reduce the level of stress among university students.